PENGARUH KEEFEKTIFAN PENGENDALIAN INTERNAL DAN KESESUAIAN KOMPENSASI TERHADAP PERILAKU TIDAK ETIS PADA PT IQOO VIVO KALIMANTAN - Rakhmi Ridhawati; Penta Lestarini Budiati; Syifa Aulia (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, This research try to give empirical evidence Of the Effect of Internal Control Effectiveness and Conensastion Convenience to Unethical Behavior at PT IQOO VIVO KALIMANTAN. Sampel in this research are employees which involve in making of reinbursement note counted 92 respondents. The result of this research indicate that internal control effectiveness and compensation convenience have an effect on negativity to unethically behavior either parsial (t test) and also simultan (F test).